A comparison of the application of block theory and 3D block-cutting analysis. (November 2017) - Zhang, Qi-Hua; Ding, Xiu-Li; Wu, Ai-Qing
Abstract: In hard rock masses, rock destruction is often manifested in the form of the local failure of the blocks formed due to fracturing. In this paper, we compare the application of block theory and three-dimensional (3D) block-cutting analysis to underground caverns. Using block theory, we can determine both the type of removable block and key block for different excavation surfaces. We can then identify 'support-required' blocks from the key blocks by drawing and analyzing the shapes of the maximum likely blocks (i.e. the largest blocks likely to be formed when the fractures are extended indefinitely in a definite-sized cavern). Subsequently, 3D block-cutting analysis is used to identify all the spatial blocks cut by all the finite-sized fractures in the rock mass region. Based on the geometrical information gathered about each spatial block, we carry out an analysis of the progressive failure of the block system. The simulation results allow us to explore the statistical laws governing the distribution of progressive failure blocks. This is a very important aspect which can be used to determine the spacing and length of the rock bolts required, or to check the design of the intended rock support regime. Overall, if we can understand the shortcomings of classic block theory (due to, for example, the assumptions made) and properly utilize the benefits gained from 3D block-cutting analysis, we can deal with more complicated issues. Thus, we hope to gain a more intensive and extensive understanding of block failure analysis.